BEDIPOLI : Implementing an Educational Game Monopoly to Enhance Digital Ethics Among Elementary School Students in Purwakarta, Indonesia - Novianti, Putri Ade; Hikmawan, Rizki; Fajrussalam, Hisny (Universitas Pendidikan Mandalika, 2025)
This research aims to enhance elementary school students’ comprehension of digital ethics by employing Monopoly as the medium for Educational Game Tools (APE). This study used a quantitative approach with a pre-experimental design featuring a one-group pre-test and post-test, with the sample selected through purposive sampling. The instrument design involved creating assessment tools validated by six experts. The learning media included 30 questions on digital ethics comprehension, with validity assessed using the content validity ratio (CVR). To test the hypothesis, a Wilcoxon Signed-Ranks Test was applied to compare the pre-test and post-test scores. Pre-test and post-test instruments were adapted from the Ministry of Communication and Information Technology’s “Status of Digital Literacy in Indonesia 2020,” focusing on communication skills and technology ethics. The results revealed that initial assessments indicated a low understanding of digital ethics among students, with 18 out of 39 needing to demonstrate mastery before the APE implementation. However, post-implementation evaluations showed that only one student did not achieve mastery, with significant overall improvement and heightened enthusiasm for learning, highlighting the APE’s effectiveness. The study suggests that incorporating educational game tools (APE) into learning methods can significantly enhance students’ understanding of digital ethics.